Die neueren Quellen von Persecutio Hungaricae - Csorba, Dávid (Acta Neerlandica, 2026)
The study focuses on the history and historiography of the Hungarian Galley Slaves. Thepublication of their story by the Western European press made a huge impact on international Calvinism. In Hungary it went the opposite way, mainly for historical reasons. Amanuscript and its large amount of copies built a great legacy, thanks to the historicalresearch for the original documents (mentioned in texts by Bálint Kocsi Csergő and FerencOtrokocsi Fóris) between the 17th and 20th century. Thus, the attitude of the Galley Slavesindeed became a decisive image of Hungarian, reformed identity.